The - edited by Richard A. King; Jerome I. Rotter; Arno G. Motulsky (Oxford University Press, 2002)
The entire book has been updated and twelve new chapters have been added. Most of these chapters deal with diseases such as gallstones, osteoporosis, osteoarthritis, skin cancer, other common skin diseases, prostate cancer and migraine headaches that are seen by all physicians. Others address the genetic and molecular basis of spondylarthropathies, lupus, hemochromatosis, IgA deficiency, mental retardation, hearing loss, and the role of mitochondrial variation in adult diseases